Avaliação das crenças sobre as práticas parentais ao recém-nascido prematuro na perspectiva das mães cuidadoras - Barros, Paula Luísa Lima Melo de (2018)
The present study aimed to evaluate the beliefs about parental practices to the premature newborn from the perspective of the caregiver mothers of the outskirts of the city of Guanambi / BA. This is an exploratory study with a qualitative approach. We interviewed 30 mothers of premature newborns, registered in the Basic Unit of the Municipality of Guanambi / BA. Three questionnaires were applied: a sociodemographic, beliefs about parental practices and a qualitative instrument. The data were evaluated using descriptive and comparative statistics. The results identified that sociodemographic factors and prematurity influence the adoption of specific parental practices for each context. The main practices adopted by the mothers studied were face-to-face contact, with an average of 8.5 (+2.6), and body stimulation, with 6.8 (+0.8) points. Mothers were the ones who took care of their children at home (36.7%), followed by grandparents (26.7%). The frequency of prenatal consultations was 93.3%, but 70.0% never participated in any type of support group and exchange of experiences. The main guidelines given to mothers during prenatal care were on vaccines (73.3%). The guidelines offered during prenatal care were classified by mothers as very important (83.3%), but they did not identify any professionals responsible for promoting the link between the family and the FHT. More than half (56.7%) of the participants did not feel prepared to take care of their children at home, as they felt fear (53.3%) and insecurity (33.3%). Mothers did not perceive a relevant contribution from the FHS (66.6%); reported family interferences regarding newborn care, but they saw this interference as positive (33.0%). It was concluded that social, cultural, environmental and, above all, prematurity contexts interfered in the adoption of parental styles and perception of parenthood. The need for new studies to increase knowledge that subsidize effective public policies with an emphasis on the care of premature newborns and the context in which they are inserted is emphasized.